Science and Scientific Arguments Regarding the Controversy About Execution of the Hidroaysén Project: Regulations, Discussions, and Procedures; [Ciência E Argumentos Científicos Na Polêmica Sobre a Instalação Do Projeto Hidroaysén: Regulamentação, Debate E Processo]; [Ciencia y Argumentos Científicos en la Controversia Sobre la Instalación del Proyecto Hidroaysén: Normativa, Debate y Proceso] - Broitman-Rojas, C; Rocamora-Villena, V (Universidad del Rosario, 2021)
The construction of a large hydroelectric project in the Chilean Patagonia sparked a discussion that faced the arguments of promoters and opponents. This article analyzes the communication strategy of main actors of this emblematic controversy, showing how both sides adapted themselves to the circumstances with different degrees of flexibility by using the scientific-technical discourse as a legitimization mark. However, as the conflict became covered by the media and positions were clearly defined, changes were observed in the way these arguments were presented. While in the case of the opponents, permanent participation of scientists is highlighted throughout the controversy; however, this was not the case with promoters. Although these expert voices, who were recruited early by the HidroAysén company, were diluted during the conflict, it can be noted that their arguments survived throughout the discussion. © 2021, Universidad del Rosario. All rights reserved.